The Eucharist in the Polish Catholic Church and the Assumptions of the Constitution Sacrosanctum Concilium - Golec, Łukasz (Studia Warmińskie, 2022)
The Polish Catholic Church in the Republic of Poland grew out of the reform group headed by Fr. Franciszek Hodur, operating in the USA at the turn of the 19th and 20th centuries, and then also in Poland. The scope of postulates for the reform of the Church raised by Hodur also included aspects of changes in the liturgy. The purpose of the article is to provide an answer to the question: how Hodur’s postulates regarding the Eucharist relate to those raised later by the Roman Catholic Church during the Second Vatican Council (1962-1965)? The research was based, on the one hand, on publications containing the thoughts of Fr. Bishop Franciszek Hodur, as well as other Old Catholic theologians, while the documents of the Second Vatican Council - first of all, the Constitution on the Sacred Liturgy and execution instructions and also the Dogmatic Constitution on the Church. Apart from external changes, postulated by the liturgical reform: the introduction of the national language into the liturgy, the possibility of celebrating Holy Mass facing the faithful and Holy Communion under both kinds, there are many similarities in the theological understanding of the Eucharist.